The fracture of good order Christian antiliberalism and the challenge to American politics - Bivins, Jason; NetLibrary, Inc. (Chapel Hill : University of North Carolina Press, 2003)
Whether picketing outside abortion clinics, speaking out at school board meetings, or attending anti-death penalty vigils, many Americans have publicly opposed local, state, or federal government policies on the basis of their religious convictions. In this book, Jason Bivins examines the growing phenomenon of Christian protest against civil authority and political order in the United States. He argues that since the 1960s, there has been a proliferation of religious activism against what the protesters perceive as government's excessive power and lack of moral principle. Calling this phenomenon "Christian antiliberalism," Bivins finds at its center a belief that American politics is based on a liberal tradition that threatens the practice of a religious life and gives government too much social and economic influence. Focusing on the Catholic pacifism of Daniel and Philip Berrigan and the Jonah House resistance community, the Christian Right's homeschooling movement, and the evangelical Sojourners community, Bivins combines religious studies with political theory to explore the common ground shared by these disparate groups. Despite their vast ideological and institutional differences, these activists justify their actions in overtly religious terms based on a rejection of basic tenets of the American political system. Analyzing the widespread dissatisfaction with the conventional forms of political identity and affiliation that characterize American civic life today, this book sheds light on the complex relations between religion and democratic society.
Includes bibliographical references (p. 201-211) and index.
Electronic reproduction.
Keywords: Christianity and politics -- United States; Liberalism -- Religious aspects -- Christianity; Political activists -- Religious life -- United States; Liberalism -- United States; Electronic books